Reconstructing Islamic Guidance and Counseling as an Integrative Framework for the Pancasila Student Profile - Hamzah Umasugi; H Tobroni; H. Abdul Hakim Jurumiah; Abdul Halik (AL-ISHLAH: Jurnal Pendidikan, 2026)
Islamic guidance and counselling (IGC) has been widely implemented in Indonesian madrasahs; however, it is often treated as a remedial service rather than an integrated pedagogical framework for character development. This study aims to reconstruct IGC as an empirical-based pedagogical framework to strengthen the Pancasila Student Profile at Madrasah Aliyah Negeri Sanana, Sula Islands. This study employed a qualitative single-case study within an interpretive paradigm. Data were collected through semi-structured interviews with the head of the madrasah, vice principals, a guidance and counselling teacher, and Islamic Religious Education teachers, supported by participant observation and document analysis. Data were analysed using thematic analysis through data reduction, display, conclusion drawing, and verification. Trustworthiness was established through source and method triangulation, member checking, and researcher reflection. The findings reveal that IGC has substantively existed in religious learning, student development programmes, and daily moral supervision but has not yet been institutionalised as a systematic pedagogical framework supported by structured planning, documented procedures, measurable character indicators, and continuous evaluation. IGC is implemented through individual counselling, group guidance, religious habituation, and collaborative mentoring, contributing to students’ religiosity, responsibility, discipline, and social empathy, while independence and critical reasoning remain underdeveloped. Based on these findings, this study reconstructs an empirical-based integrative pedagogical framework linking Islamic values, Islamic Religious Education, spiritual-psychological-social counselling, collaborative mentoring, and character-based evaluation. The framework is proposed as a conceptual reconstruction to support holistic character development aligned with the Pancasila Student Profile and requires further validation across diverse madrasah contexts.